2010
DOI: 10.1039/b923527m
|View full text |Cite
|
Sign up to set email alerts
|

Do solvation layers of ionic liquids influence electrochemical reactions?

Abstract: In this discussion paper we discuss our recent results on the electrodeposition of materials and in situ STM/AFM measurements which demonstrate that ionic liquids should not be regarded as neutral solvents which all have similar properties. In particular, we focus on differences in interfacial structure (solvation layers) on metal electrodes as a function of ionic liquid species. Recent theoretical and experimental results show that conventional double layers do not form on metal electrodes in ionic liquid sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
220
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(229 citation statements)
references
References 30 publications
6
220
0
3
Order By: Relevance
“…[ 40,41,42].For the Au(111) │ BMIPF 6 interface, the existence of interior and exterior layers next to the surface was reported. Here, the interior layers reveal a distinct reduced layer thickness and need a much stronger force to be ruptured [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 40,41,42].For the Au(111) │ BMIPF 6 interface, the existence of interior and exterior layers next to the surface was reported. Here, the interior layers reveal a distinct reduced layer thickness and need a much stronger force to be ruptured [42].…”
Section: Discussionmentioning
confidence: 99%
“…Atkin et al and Zhang et al detected several ionic-liquid layers in front of the electrode by measuring AFM force curves [40][41][42]. [ 40,41,42].For the Au(111) │ BMIPF 6 interface, the existence of interior and exterior layers next to the surface was reported.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The popularity of ILs as a research topic is reflected in the numerous reviews, 1,10,22 monographs, 6 and conference proceedings [23][24][25] that have been published recently. The reviews by Hamaguchi and Ozawa 26 and Kobrak, 27 as well as several journal special issues [28][29][30] have focused primarily on the physical chemistry and chemical physics of ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that solvation layers are formed on IL/solid interfaces. [7][8][9][10]28,29 If they were also formed on the HD-SAM/EMI-Tf 2 N interface, there is possibility that the tip scanned on solvation layer formed on the HD-SAM when ¦f was small. After that, ¦f was increased to +50 Hz and the tip scanned the inside of the solvation layer, where the topographic feedback became unstable.…”
Section: Time Response Of Pm-afmmentioning
confidence: 99%
“…Recently, several force curve studies on IL/solid interfaces using contact-mode AFM have been reported and they have revealed the presence of the solvation layers on the interface. [7][8][9][10] Nevertheless, contact-mode AFM has disadvantage on lateral resolution and in fact, high-resolution lateral imaging on IL/solid interfaces was mainly carried out by scanning tunneling microscopy (STM). It is well known that STM is capable of atomic-resolution imaging on conductive materials such as metals and semiconductors.…”
Section: Introductionmentioning
confidence: 99%